ANALYSIS OF JUDICIAL PROCESSES TOWARD THE CRIMINAL ACTIONS OF CORRUPTION IN DEFENDANT CONDITIONS IN ABSENTIA IN ISLAMIC LAW PRESPECTIVES - Andry Syafrizal Tanjung (Proceeding International Seminar of Islamic Studies, 2021)
Islamic law in the legal system in Indonesia is one of the positive laws that apply in Indonesia. Islamic law is adhered to and obeyed by Muslims who are the largest population in Indonesia.In practice, Islamic law is one part of the applicable law in Indonesia, which has a very important and decisive role in regulating the life of the Indonesian nation.The state-society built by the Prophet SAW has provided some background and initial models of instruments and institutions that are important pillars of the existence of a state-society.So if from the perspective of modern constitutional science, there are three institutions of state power known as triaspolitica, namely the power of the legislative, executive and judiciary institutions, it turns out that Rasulullah SAW has practiced these three forms of institutions. Corruption is an extraordinary crime, has a systemic and widespread impact and has been placed as a violation of the economic and social rights of the people. It is not uncommon for perpetrators of criminal acts of corruption to run away during the trial process of corruption cases. If you look at it from the aspect of benefiting the Indonesian people as direct victims of the criminal act of corruption. Therefore, the trial process must continue even if the defendant runs away or is not present / in absentia.Keywords: Analysis, Corruption Crime, Defendant In Absentia, Islamic Law